Looking for experts (a call for essays) - Gilbert, Susan (The Hastings Center report, 2015)
Genetic research powered by social media has the potential for great benefit: to quickly and inexpensively gather the massive amounts of data that are essential for understanding the genetic basis of diseases. But what are the ethical soft spots or gaps? I invite readers to write commentaries on this question for the blog of the Hastings Center Report.